Assessment of the biogeographical variation of seed size and seed oil traits in wild Silphium integrifolium Michx. genotypes. Issue 5 (10th October 2019) - Reinert, Stephan; Van Tassel, David L.; Schlautman, Brandon; Kane, Nolan C.; Hulke, Brent S.
Abstract: Silphium spp. have garnered interest in Europe as a bioenergy crop and in North America as a perennial oilseed crop. However, very little has been done at this early stage of domestication to characterize wild collections for many key characteristics, including important oilseed traits. The objective of this work was to develop a basic understanding of how biogeography and associated population genetic forces have shaped seed phenotypes in plant collections across the native range of Silphium integrifolium Michx. (Asteraceae: Heliantheae), the primary domestication candidate for oilseed use. A collection of 53 accessions was grown in a common environment in Salina, KS, which is a location well within the native range of the species in central North America. Plants from each collection site were randomly mated by hand to produce seed representative of each accession, and the seeds subjected to seed dimensional trait, oil content and oil composition analyses. Kernel width varied along a latitudinal cline of collection site, while kernel length varied across a longitudinal cline. Palmitic and linoleic acids were inversely correlated with each other and varied along a longitudinal cline of the collection site. The results indicate that accessions collected from more southwesterly sites tended to have larger seed and those from more westerly sites had higher linoleic acid content and lower palmitic and myristic acids, which are all desirable phenotypes for an oilseed Silphium .